Jugular foramen tumor causing isolated hypoglossal nerve palsy: a case report - Wen, Zhijun; Li, Youcheng; Cheng, Jianhua; Huang, Yirui (Frontiers in Oncology, 2026)
BackgroundThe etiology of hypoglossal nerve palsy is diverse, including trauma, infection, tumors, endocrine disorders, autoimmune diseases, and vascular lesions. Tumors in the jugular foramen region are rare and primarily include paragangliomas, schwannomas, or meningiomas. Isolated hypoglossal nerve palsy caused by a jugular foramen tumor is exceedingly rare. This report presents a unique case of a jugular foramen tumor leading to isolated hypoglossal nerve injury.Case reportA 39-year-old male with no significant medical history presented with a two-week history of headache and 10 days of leftward tongue deviation. Physical examination revealed leftward tongue deviation with mild dysarthria. Nasopharyngoscopy and routine laboratory tests yielded normal results. Lumbar puncture and next-generation sequencing (NGS) ruled out intracranial infection. MRI showed a 6.0×9.0 mm nodule in the left jugular foramen, hyperintense on T2-weighted imaging, isointense on DWI, and exhibiting ring-like enhancement on contrast MRI. A jugular foramen tumor was suspected, and surgical resection was recommended. However, the patient opted for gamma knife treatment at another hospital, resulting in symptom improvement.Results and conclusionMultisequence MRI confirmed compression of the hypoglossal nerve by a left jugular foramen tumor. This case is unique in that the tumor, despite its location, manifested solely as hypoglossal nerve palsy, an atypical presentation that can lead to misdiagnosis. This case report highlights the importance of high-resolution imaging and multidisciplinary collaboration in diagnosing skull base lesions and explores the anatomical relationship between the hypoglossal nerve and jugular foramen in disease pathogenesis.